The Effect of Social Capital Relations and Community Participation in the Development of the Bejijong Tourism Village, Indonesia - Arizkha, Yulia Faizatul; Prayitno, Gunawan; Dinanti, Dian; Biloshkurskyi, Mykola V.; Hiddlestone-Mumford, Jacqueline; Illingworth, Juianita; Pant, Satish Chandra; Atkinson, Chris; Li, Sasha (Journal of Regional and Rural Studies, 2023)
Tourism is one of the government's leading sectors that contributes significantly to the country's foreign exchange receipts. One of the strategies of the tourism sector to continue to trigger economic growth is to develop sustainable tourism through the Tourism Village program. Tourism village development requires the collective involvement of local communities to ensure the program's sustainability. The availability and utilization of social capital influence community participation in tourism development.  This study aims to identify how social capital affects community participation in developing the Bejijong Tourism Village program. The population in this study includes the heads of families of tourism actors, with a total sample of 279 households. The variables used are social capital variables consisting of social networks, trusts, social norms, and participation variables at the implementation stage.  The analysis used is the Structural Equation Model (SEM) to determine the constituent factors contributing to each variable, thereby facilitating an understanding of the specific factors that merit attention for improvement and those that should be upheld to optimize tourism performance. The results of the analysis show that social capital significantly influences community participation. The better the social capital in Bejijong Village, the more people will be willing to participate in developing tourism villages. The social capital variable with the highest influence on participation is the trust variable. Therefore, the community must uphold the optimality of factors influencing trust for the sustainability of tourism development.